2017
DOI: 10.1161/circep.116.004422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Substrate Modification by Catheter Ablation on Implantable Cardioverter–Defibrillator Interventions in Patients With Unstable Ventricular Arrhythmias and Coronary Artery Disease

Abstract: Background— The implantable cardioverter–defibrillator (ICD) is the standard therapy to prevent sudden cardiac death in patients with coronary artery disease and unstable ventricular tachyarrhythmias. The prospective multinational SMS (Substrate Modification Study) was designed to assess whether prophylactic ablation of the arrhythmogenic substrate reduces or prevents the recurrence of ventricular tachycardia/ventricular fibrillation in such patients. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 20 publications
(21 reference statements)
2
105
0
1
Order By: Relevance
“…The first implication is that prophylaxis of shocks and ATP by recommending a strategy that mitigates the likelihood of ventricular arrhythmia in patients with ICDs may have mortality implications. Two randomized trials have evaluated the effect of prophylactic ventricular tachycardia catheter ablation as an addition to ICD in the ischemic cardiomyopathy population . Although the findings of those trials cannot be extrapolated to our population, one could hypothesize that decreasing the burden of shocks or delaying the appearance of ventricular arrhythmia could translate into a better survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first implication is that prophylaxis of shocks and ATP by recommending a strategy that mitigates the likelihood of ventricular arrhythmia in patients with ICDs may have mortality implications. Two randomized trials have evaluated the effect of prophylactic ventricular tachycardia catheter ablation as an addition to ICD in the ischemic cardiomyopathy population . Although the findings of those trials cannot be extrapolated to our population, one could hypothesize that decreasing the burden of shocks or delaying the appearance of ventricular arrhythmia could translate into a better survival.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized trials have evaluated the effect of prophylactic ventricular tachycardia catheter ablation as an addition to ICD in the ischemic cardiomyopathy population. 20,21 Although the findings of those trials cannot be extrapolated to our population, one could hypothesize that decreasing the burden of shocks or delaying the appearance of ventricular arrhythmia could translate into a better survival. The second clinical implication of our study is that patients presenting with an appropriate shock or ATP whether they received an automatic implantable cardioverter/defibrillator for primary or secondary indication has mortality implications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in the management of predisposing conditions, especially coronary artery disease (CAD), the incidence of VT has increased when comparing older RCTs where the recurrence rate was 33% to contemporary RCTs which has a recurrence rate between 42%‐45% . In those with idiopathic VT, a recent population‐based study found rates had increased from 12.7 to 16.2 (per 100 000) over a 6‐year period .…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in the management of predisposing conditions, especially coronary artery disease (CAD), the incidence of VT has increased when comparing older RCTs where the recurrence rate was 33% 5 to contemporary RCTs which has a recurrence rate between 42%-45%. 7,8 In those with idiopathic VT, a recent population-based study found rates had increased from 12.7 to 16.2 (per 100 000) over a 6-year period. 22 Paralleling increasing rates of VT is recent local data showing a three-fold increased rate of ICD implantation over a similar period 3 that incurs significant additional costs on the healthcare system.…”
Section: Possible Explanations For Temporal Trends In Vt Ablations mentioning
confidence: 99%
See 1 more Smart Citation